Global environmental biotechnology proceedings of the Third Biennial Meeting of the International Society for Environmental Biotechnology, 15-20 July 1996, Boston, MA, U.S.A - International Society for Environmental Biotechnology Meeting 1996 : Boston, Mass.); Wise, Donald L. (Donald Lee), 1937- (Amsterdam ; New York : Elsevier, 1997)
Environmental biotechnology is an emerging field of scientific and technological investigations that is truly global. Popular recognition is high for the environmental problems being faced and solved by biotechnology methods. This book presents selected papers from the 3rd International Symposium of the International Society for Environmental Biotechnology, held in Boston in July 1996. The following topics are covered: metals, mine drainage, removal and toxicity; waste treatment/monitoring; bioremediation; water quality; biodegradation; and local, national and international issues in biotechnology.
Section headings: Metals: Mine Drainage, Removal, Toxicity. Waste Treatment/Monitoring. Bioremediation: In situ/Rectors/Basic Studies. Water Quality. Biodegradation. Local, National, International Issues. Keyword index.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Bioremediation; Electronic books